Hydroesterification of 2-vinyl-6-methoxynaphthalene using palladium complexes containing chelating nitrogen ligands - Atla, Shashi B.; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2009)
Hydroesterification of 2-vinyl-6-methoxynaphthalene (VMN) to methyl ester of 6-methoxy naphthyl propionic acid (ester of naproxen) has been investigated using palladium complexes containing the chelating N(boolean AND)O and N(boolean AND)N ligands (pyridine-2-carboxylate, 2-acetylpyridine, 2-pyridine-carboxaldehyde, and bipyridine) as catalysts. Palladium complex containing 2-acetylpyridine as the ligand was found to be superior to other Pd-complexes. Both acid and halide promoters were necessary for high activity and selectivity. As an acid promoter, benzenesulfonic acid was found to be more effective compared to p-toluenesulfonic acid. Formation of ether 2-methoxy-6-(1-methoxyethyl)naphthalene and a polymer of VMN was observed in all the reactions. It was observed that active catalytic species generated during carbonylation reaction was responsible for the polymer formation. The effect of various parameters such as solvents, CO pressure, and alcohols on the catalytic activity as well as the selectivity was investigated. The turnover frequency using the complex Pd(acpy)(PPh(3))(OTs)(2) (acpy = 2-acetylpyridine) catalyst was found to be 42 h(-1), which is the highest for the hydroesterification of VMN. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Carbonylation; Hydroesterification; Naproxen; Palladium complex; Polymer of VMN; Promoters

Kinetics of arylation of 3-bromo-benzophenone with n-butylacrylate using NC palladacycle catalyst - Atla, Shashi B.; Rajurkar, Kalpendra B.; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2009)
The kinetics of arylation of n-butylacrylate (n-BA) with 3-bromo-benzophenone (BBP) using a monomeric palladacycle complex [Pd(ppy)(PPh(3))(OTs)](ppy=2-phenylpyridine) catalyst has been studied. The effect of concentration of the substrate, base (NaOAc), and catalyst was studied at three different temperatures (413-433 K). The rate was found to be first order with respect to catalyst, first order tending to zero order with respect to n-butylacrylate and NaOAc concentrations. The rate passed through a maximum with variation of BBP concentration. The observed results have been explained on the basis of formation of Pd species (PdX(2), PdX(3)(-), PdX(4)(2-), and Pd(2)X(6)(2-)) which are inactive for the Heck reaction. Various empirical rate equations were considered to fit the rate data and the best fitting model has been selected. The rates predicted by model were found to be in good agreement with the observed experimental data. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Arylation; Heck reaction; kinetics; Palladacycle

NC palladacycles in the Heck arylation of ethylene: synthesis, structure and their reactivity - Atla, Shashi B.; Kelkar, Ashutosh A.; Puranik, Vedavati G.; Bensch, Wolfgang; Chaudhari, Raghunath V. (Journal of Organometallic Chemistry, 2009)
Monomeric cyclopalladated complexes with NC coordination using ligands 2-phenylpyridine, 2-phenylquinoline, 8-methylquinoline have been synthesized and the structures have been determined by single crystal X-ray structure analysis. The crystal structures of monomeric palladacycles prepared using benzophenone oxime, and 2-phenylpyridine have also been determined. The use of these complexes in the Heck arylation of ethylene with 2-bromo-6-methoxynaphthalne (BMN) to give 2-vinyl-6-methoxynapthalene which is an intermediate for the synthesis of anti-inflammatory drug Naproxen has been examined and also arylation of ethylene with 3-bromo-benzophenone and 4-bromo-isobutylbenzene was investigated. These palladacycles with NC coordination show excellent catalytic activity with a TOF > 4000 h (1). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Aryl propionic acids; Arylation; Palladacycle